Catalyst degradation diagnostics of proton exchange membrane fuel cells using electrochemical impedance spectroscopy. (19th July 2018) - Pivac, Ivan; Bezmalinović, Dario; Barbir, Frano
Abstract: A previously validated equivalent circuit model, in which two resonant circuits were inserted to represent the processes in the catalyst layers, is applied to fit the electrochemical impedance spectroscopy results of a single proton exchange membrane fuel cell exposed to accelerated stress test targeting catalyst degradation. The simulation results of the applied equivalent circuit model show very good agreement with the experimental data. The applied model is able to extract contributions of each of the model elements to the cell degradation. The obtained results indicate that the cathode catalyst layer resonant loop parameters, together with the cathode charge transfer resistance and cathode double-layer capacitance, change the most during the accelerated stress test. If each of the elements of the cathode resonant loop can be associated with physical processes inside the catalyst layer, the model may be used to give more insight into the degradation effects on functioning of the catalyst layer. From the conducted electrochemical impedance spectroscopy analysis, it seems that the low-frequency intercept in Nyquist plot shows the most significant change with degradation, so it may be used directly as a sufficient indicator of fuel cell performance degradation due to catalyst layer degradation. Highlights: Electrochemical impedance spectroscopy used to characterize PEM fuel cell degradation. A resonant loop used to represent the processes in the catalyst layer. Elements of the cathode resonant loop changed the most during accelerated stress test. Low-frequency intercept shows the most significant change with degradation. Low-frequency intercept may be used as an indicator of fuel cell degradation.